The impact of organizational structure on the internationalization strategy - Nerman Ljevo; Aziz Šunje (Economic Review: Journal of Economics and Business, 2021)
The organization has certain characteristics that both man and other living beings have. These include the primary basic types of organization, or organizational configurations, as well as organizational context variables such as environment, power, age, size, business strategy, and technical system. The main research about organizational structures was started by Mintzberg in 1979. After that, many other authors made a research on this topic. Organizational management is first determined by the organization's configuration and then, by the type of strategy for entering the international market. The paper examines the extent to which the choice of organizational configuration has an impact on the choice of the internationalization strategy or the strategy for entering a foreign market. The research sample consists of 120 export-oriented companies from Bosnia and Herzegovina belonging to one of the four basic types: simple structure, professional bureaucracy, adhocracy, or machine bureaucracy. The basic methods used are the Multinomial Logit Model, the multiple regression model, and the Pearson correlation coefficient. The results of the research indicate that there is a significant correlation between organizational configuration (measured by organizational context variables) and internationalization strategy.
Keywords: L1; F; 330; configuration; structure; internationalization; strategy; organization